Q1291H-CFTR molecular dynamics simulations and ex vivo theratyping in nasal epithelial models and clinical response to elexacaftor/tezacaftor/ivacaftor in a Q1291H/F508del patient - Allan, Katelin M.; Astore, Miro A.; Kardia, Egi; Wong, Sharon L.; Fawcett, Laura K.; Bell, Jessica L.; Visser, Simone; Chen, Po-Chia; Griffith, Renate; Jaffe, Adam; Sivam, Sheila; Vittorio, Orazio; et al. (Frontiers in Molecular Biosciences, 2023)
Background: Cystic fibrosis (CF) is caused by a wide spectrum of mutations in the CF transmembrane conductance regulator (CFTR) gene, with some leading to non-classical clinical presentations. We present an integrated in vivo, in silico and in vitro investigation of an individual with CF carrying the rare Q1291H-CFTR allele and the common F508del allele. At age 56 years, the participant had obstructive lung disease and bronchiectasis, qualifying for Elexacaftor/Tezacaftor/Ivacaftor (ETI) CFTR modulator treatment due to their F508del allele. Q1291H CFTR incurs a splicing defect, producing both a normally spliced but mutant mRNA isoform and a misspliced isoform with a premature termination codon, causing nonsense mediated decay. The effectiveness of ETI in restoring Q1291H-CFTR is largely unknown. Methods: We collected clinical endpoint measurements, including forced expiratory volume in 1 second percent predicted (FEV1pp) and body mass index (BMI), and examined medical history. In silico simulations of the Q1291H-CFTR were compared to Q1291R, G551D and wild-type (WT)-CFTR. We quantified relative Q1291H CFTR mRNA isoform abundance in patient-derived nasal epithelial cells. Differentiated pseudostratified airway epithelial cell models at air liquid interface were created and ETI treatment impact on CFTR was assessed by electrophysiology assays and western blot. Results: The participant ceased ETI treatment after three months due to adverse events and no improvement in FEV1pp or BMI. In silico simulations of Q1291H-CFTR identified impairment of ATP binding similar to known gating mutants Q1291R and G551D-CFTR. Q1291H and F508del mRNA transcripts composed 32.91 % and 67.09 % of total mRNA respectively, indicating 50.94 % of Q1291H mRNA was misspliced and degraded. Mature Q1291H-CFTR protein expression was reduced (3.18 ± 0.60 % of WT/WT) and remained unchanged with ETI. Baseline CFTR activity was minimal (3.45 ± 0.25 µA/cm2) and not enhanced with ETI (5.73 ± 0.48 µA/cm2), aligning with the individual’s clinical evaluation as a non-responder to ETI. Conclusion: The combination of in silico simulations and in vitro theratyping in patient-derived cell models can effectively assess CFTR modulator efficacy for individuals with non-classical CF manifestations or rare CFTR mutations, guiding personalized treatment strategies and optimizing clinical outcomes.